HUBUNGAN FAKTOR RISIKO PENCEMARAN DAN KUALITAS AIR SUMUR GALI SECARA MIKROBIOLOGIS DENGAN KEJADIAN DIARE DI DESA HUTABARINGIN KECAMATAN KOTANOPAN KABUPATEN MANDAILING NATAL - nuraini hayati; evi naria; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
Clean water is a basic need that must be met by a human because clean water is used for various purposes including as drinking water. The source of clean water which is mostly used by society is dug well. Dug wells is easily contaminated by bacterial from the source of pollution. It can cause the disease like diarrhea. For get clean water that meets health requirements it must avoid from the risk factors of pollution that can be at risk of water quality of dug well. The purpose of this research was to know correlation between the risk factors of pollution and the quality of bacterial water of dug with the incidence of diarrhea in Village Hutabaringin District Kotanopan Regency of Mandailing Natal. This research used the analytic with cross-sectional design. With taking sample by random sampling (simple random sampling ) is a random number table system with a sample of 55 households. This population is all households in the village have dug well Hutabaringin Kotanopan the District, totaling 121 households. Data were analyzed using chi-square test. The results showed that most households have dug wells which have a high pollution risk factors is 54,5% , low is 45,5. The number of households that have water quality that meets the health requirements is 38,2% and which do not meet the health requirements is 61,8%. Diarrhea happened in every family member is 61,8% and who did not diarrhea happened is 38,2%. Based on the results of research by chi-square test p = 0.025 ( p < 0.05 ) it can be concluded that correlation the are pollution risk factors with diarrhea happened and p = 0.009 (p < 0.05) correlation the are water quality dug well with diarrhea happened. It is recommended to the public in order to better maintain the quality of well water as a source of clean water and basic sanitation especially pay attention to clean water and personal hygiene. Puskesmas should be made the socialization to the society within programs in water supply and environment health. Keywords : Risk factors of pollution, the quality of bacteriological water, diarrhea